Chinese Medicine Syndromes in Congestive Heart Failure： A Literature Study and Retrospective Analysis of Clinical Cases - 李小茜 何建成 黄品贤 曹雪滨 (Chinese journal of integrative medicine, 2016)
Objective： To discuss the characteristics of Chinese medicine （CM） syndrome factors and distribution of congestive heart failure （CHF）, and provide a basis for the diagnosis criteria of essential syndromes. Methods： Based on databases of China National Knowledge infrastructure （CNKI, 1980--2012） and Chinese Journal of Chongqing VlP Database （1989-2012）, the eligible studies in CHF and extracted factors associated with compound syndromes were analyzed. All the syndromes were classified into deficiency, excess, and deficiency-excess in complexity syndrome were classified. Compound syndromes were separated into syndrome factors including single, double, three or four factors, along with the frequency of occurrence. The relation of CHF syndromes with age, gender, primary disease, brain natriuretic peptide （BNP） and cardiac functional grade was studied in 1,451 CHF cases （between December 2010 and September 2012）, and the clinical distribution of common CHF syndromes was summarized. Results： The literature study involved 6,799 CHF cases in 66 literatures after screening. Of the different factors affecting CHF, qi deficiency was the most important one. In deficiency syndrome, Xin （Heart）-qi-deficiency was the most common single factor, and deficiency of both qi and yin was the most common double factor. The retrospective analysis involved 1,451 CHF cases （431 cases with test results of BNP）. The xin blood stasis and obstruction and deficiency of both qi and yin syndrome were mostly seen in female patients, and phlegm-blocking-Xin-vessel and qi-deficiency-blood-stasis syndrome mostly in males. Xin-qi-deficiency and qi-deficiency-blood-stasis syndrome were mostly seen in patients aged 50--60 years. Patients aged over 60 years likely manifest deficiency of both qi and yin and Xin blood stasis and obstruction syndrome. The severity of syndrome is aggravated with increased BNP and cardiac functional grade. Conclusions： The essential syndromes of CHF include qi-deficiency-blood-stasis and deficiency of both qi and yin. The clinical distribution is linked to patients＇ age and gender. BNP and cardiac functional grade is closely related to CHF syndromes, which may indicate the severity of CM syndromes of CHF.